DESIGN OF BOTANICAL GARDEN IN IBU KOTA NUSANTARA TO SUPPORT REFORESTATION OF KALIMANTAN'S TROPICAL FOREST IN ALIGNMENT WITH THE FOREST CITY DEVELOPMENT CONCEPT - Karla, Olivia
Ibu Kota Nusantara (IKN) is located in North Penajam Paser Regency and Kutai Kartanegara, East Kalimantan, and has an area of 256,142 acres with varied land cover. As a result, current conditions must be analyzed by examining the land cover and topography of the IKN area, as well as spatial planning based on existing conditions. Remote sensing methods with Sentinel-2A satellite photos were used to analyze existing conditions. Dense and medium vegetation predominate, covering an area of 109,218 ha (38.4%) and 98,873 ha (34.8%), respectively, with a normalized difference vegetation index (NDVI) value of 0.6 - 1. There is also mining land (10.3%) and open land (6.8%). The IKN area has 2.1% settlements and 10.3% agricultural or plantation land. The area's dominant slope is flat (0 - 8%), spanning an area of 1883.7 ha, followed by a mild slope (8 - 15%), covering an area of 723.8 ha. The predominant elevation is from 25 to 100 meters above sea level. The main water sources, the Sepaku and Mahakam rivers, have riparian zones dominated by dense and medium vegetation cover, which is 62.4%, followed by agriculture and plantations at 230.6 ha (10%). The results of land cover and topographic analysis, as well as the status of riparian zones, can serve as basic restrictions in returns, particularly for green open spaces, when carrying out development and serve as a reference and consideration when carrying out development. According to Peraturan Presiden Nomor 63 dan 64 Tahun 2022, there are areas that have the potential to be built botanical gardens, namely in the jungle zone in the Core Area of the Capital City Government Center of the Archipelago, with existing land cover of medium and dense vegetation, a dominant height of 7-100 meters above sea level, and flat to gentle slopes.